The coal origin-destination matrix analysis and multimodal transportation cost modelling in the Yangtze River region, China. Issue 2 (20th July 2018) - Wan, Yu; Li, Wenjie
ABSTRACT: The railway-road-inland waterway (IWW) transportation network in the Yangtze River basin was extracted using ArcGIS software and the triangular mesh covered the simulated region was generated using GIS software. The population density and gross domestic product were chosen as the characteristic economic variables, which were interpolated spatially into the mesh to analyse the origin-destination (OD) matrix of the coal transport network. Then, the multimodal transportation cost model was developed considering the detailed cost functions of railway, road and IWW. Finally, the coal transportation cost under different transportation allocation scenarios was calculated and compared to investigate the advantages and potential of the multimodal transportation mode in the Yangtze River basin. The cost analysis about the multimodal transportation system showed that the IWW mode has great potential to decrease the transportation cost of the coal within the OD matrix although the railway mode took at least 80% of the total transportation load.